THE REPRESENTATION OF EGYPTIAN PEOPLE’S VOICE IN THE JAKARTA GLOBE NEWS PHOTOGRAPHS - Fitriani, Fini; Sukyadi, Didi; Muhammad, Ahsin (Universitas Pendidikan Indonesia, 2012)
Abstract: As a product of mass media, news photograph is an image which provides the viewers with a valuable source of information and news story. All events captured in photographs turn into a news photo. Besides covering the news with fact, news photographs do not only have surface meanings, but also deeper meanings to be interpreted by each viewer. The phenomenon of demonstration, particularly the massive demonstration in Egypt in 2011, offers a good chance to discover how visual messages have been presented to guide interpretation of foreign news events. Principally, demonstration is an expression of the people’s voices, and thus, their voices are related closely with their demands, grievances and wishes related to the new government. Here, the photographs are able to portray and reflect the people’s voices through the compositions and contents (meanings) involved in the photos. This study is aimed at discovering the portrayal of the voice of the people (the protesters) in the news photographs of the Indonesian online newspaper, The Jakarta Globe. The data consist of 15 news photographs taken from The Jakarta Globe online newspaper published in January – October 2011. The study employs qualitative method framed with semiotic analysis using Roland Barthes’ theory of orders of signification and photographic message. The results of the study show that The Jakarta Globe visually constructs this event (demonstration) by focusing on the human action (the protesters). Thus, the voice of the people is portrayed in the photo subjects (the protesters) and the included objects of the photo. Meanwhile, the technical aspects of the photos play a meaningful role in emerging the portrayal of the people’s voice. There are four voices revealed by the people in the 15 photographs, namely the voice of freedom, the voice of peace, the voice of justice and the voice of human rights. The photo text including headlines and captions also interact with photographs to produce meaning in supporting the people’s voices. The headlines tend to explain the people’s voices implicitly, while the captions tend to explain the people’s voices explicitly. Keywords: people’s voice, news photograph, headline, caption, semiotic